(untitled) (Fiep Bulletin - online, 2011)
The Metabolic Syndrome (MS) is represented by a group of Risk Factors (RF): cardiovascular and genetic predisposition, the inadequate feeding and the physical inactivity constitute the main factors for development. The National Cholesterol Education Program - Adult Treatment Panel III (NCEP-ATP III). MS corresponds to the combination of the following components: Blood pressure (AP), Central Obesity (CO), Triglycerides (TGs), HDL - Cholesterol and Glycemia of Fast (FG). This work had as its main objective to draw the profile of bearers of participant MS of the Program of Pharmaceutical Attention of UEPB (PROATENFAR) during the period of April to May of 2007 and it was treated as a longitudinal and documentation study with a quantitative approach. Of the 110 bearers, 73% were women, and the age group more prevalent corresponded to 60-69 years old and 75% of them presented Systemic Arterial Hypertension (SAH). The most frequent components of MS were: OC (84%), HDL-cholesterol (83%) and TGs (70%). Regarding the medicines most used: the anti-hypertensive, anti-hypertensive, hypoglicemiates, anti-hypertensive and hypolipemiantes, the ones most prescribed. The participants of the research with Cardiovascular Diseases need activities to motivate the change to healthier habits and the pharmacotherapy, reducing the possibility of Cerebral Vascular Accident (CVA), Sharp Infarct of Myocardium (SIM) or other complication that results in a disability or in death.